In situ dynamic rheological analysis of raw yam tubers: a potential phenotyping tool for quality evaluation - Otegbayo, Bolanle Omolara; Tran, Thierry; Ricci, Julien; Gibert, Olivier (Wiley, 2024)
Most rheological analyses in yam have been done on starch gels, which requires starch extraction from the tubers. In situ rheology bypasses the need of starch extraction and relies on the original cell structure and complex matrix organization under stress or strain. Dynamic rheological properties of tuber from 16 accessions belonging to four yam species (Dioscorea rotundata, D. alata. D. bulbifera and D. dumetorum) were investigated for potential use as a medium throughput phenotyping screening tool that can indicate the quality of yam food products or their industrial potentials.Rheographs of the tubers illustrated differences in the structure of D. bulbifera compared to other yam species. High initial storage modulus (G') of yam parenchyma indicated tubers with strong and rigid structure which do not lose their structural integrity easily on heating. Dioscorea rotundata and D. alata varieties exhibited a lower temperature at which gelatinization took place (Tgel ) equivalent to the irreversible transition during starch gelatinization (75.3 and 79.8 °C) and took shorter time (867 and 958 s, respectively) to reach the G' maximum, compared to other species. The stress relaxation test showed that the higher the dry matter of the tubers, the higher the work to rupture the structure.Rheological characteristics G', loss modulus (G″), swelling capacity and Tgel showed potential as suitable quality indicators for yam products. In situ rheological characterization of yam tubers could be used as an instrumental screening tool to phenotype for quality in yam products. © 2023 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.